Anatase titania nanoparticles for covering P3HT microfibers: Morphological properties. Issue 1737 (16th June 2015) - Díaz-Cruz, Evelyn B.; Hernandez, Diego; Nicho-Díaz, M.E.; Martínez-Alvarez, Omar; Zhao-Hu, Hailin; Martínez-Alonso, Claudia; Arenas-Arrocena, M.C.
ABSTRACT: Anatase titania has been widely used for several applications such as photocatalysis and solar cells. Sol-gel is a conventional route to obtain amorphous titania and, either post-annealing or a post-hydrothermal treatment are necessary to obtain anatase crystalline phase. It is well known that the synthesis conditions affect in the particle size, surface area and grain size of the titania. In this work regular nanoparticles of anatase titania (TiO2 ) were obtained by an easy ultrasound-assisted synthesis; the nanoparticles were undergone to either a hydrothermal treatment at 130 °C and/or to an annealing at 450°C. Nanoparticles powder with a crystal size of about 8-10 nm were re-dispersed in aqueous solution at different concentrations (5 to 20mg/mL). Poly (3-hexylthiophene) (P3HT) microfibers were immersed into the TiO2 nanoparticles solution for 24 h and they were dried at 80°C for 1 h in order to form the bulk heterojunction. P3HT:TiO2 heterojunctions were characterized by SEM and EDS. According to SEM results at low concentration (5 mg/mL), the covering of the P3HT microfibers is poor and at high concentration (20 mg/mL) the microfibers were seen cracked. The best homogeneous covering onto the P3HT microfibers was obtained at 10mg/mL of titania nanoparticles; it could be the optimal concentration to build bulk heterojunction for hybrid solar cells.